Marked variation in newborn resuscitation practice: a national survey in the UK - Mann, Chantelle; Ward, Carole; Grubb, Mark; Hayes-Gill, Barrie; Crowe, John; Marlow, Neil; Sharkey, Don (Elsevier, 2012)
Abstract Background Although international newborn resuscitation guidance has been in force for some time, there are no UK data on current newborn resuscitation practices.